(untitled) (Al-Academy, 2023)
The era after World War II witnessed a remarkable transformation in the formal structure of contemporary sculpture and demonstration techniques, with its new intellectual and cognitive frameworks full of rapid and successive changes of new artistic movements and trends that provided forms, formats, new relationships and different compositional systems that included simplifications, some of which tend towards complexity, so the current study aimed to identify the aesthetics of simplification and complexity in contemporary sculpture according to postmodern concepts, The problem of the research was to answer the following question: What is the aesthetics of simplification and complexity in contemporary sculpture, this research relied on the descriptive analytical approach being the most appropriate approach to achieve the goal of the research, the research sample (3 samples) were deliberately selected to suit the privacy of the current research, and the researchers have designed (analysis form) and the most important results reached by the researchers: